From source to sink in central Gondwana: Exhumation of the Precambrian basement rocks of Tanzania and sediment accumulation in the adjacent Congo basin. Issue 9 (16th September 2016) - Kasanzu, Charles Happe; Linol, Bastien; de Wit, Maarten J.; Brown, Roderick; Persano, Cristina; Stuart, Finlay M.
Abstract: Apatite fission track (AFT) and (U‐Th)/He (AHe) thermochronometry data are reported and used to unravel the exhumation history of crystalline basement rocks from the elevated (>1000 m above sea level) but low‐relief Tanzanian Craton. Coeval episodes of sedimentation documented within adjacent Paleozoic to Mesozoic basins of southern Tanzania and the Congo basin of the Democratic Republic of Congo indicate that most of the cooling in the basement rocks in Tanzania was linked to erosion. Basement samples were from an exploration borehole located within the craton and up to 2200 m below surface. Surface samples were also analyzed. AFT dates range between 317 ± 33 Ma and 188 ± 44 Ma. Alpha (Ft)‐corrected AHe dates are between 433 ± 24 Ma and 154 ± 20 Ma. Modeling of the data reveals two important periods of cooling within the craton: one during the Carboniferous‐Triassic (340–220 Ma) and a later, less well constrained episode, during the late Cretaceous. The later exhumation is well detected proximal to the East African Rift (70 Ma). Thermal histories combined with the estimated geothermal gradient of 9°C/km constrained by the AFT and AHe data from the craton and a mean surface temperature of 20°C indicate removal of up to 9 ± 2 km of overburden since the end of Paleozoic. The correlation of erosion of the craton and sedimentation and subsidence within the Congo basin in the Paleozoic may indicate regional flexural geodynamics of the lithosphere due to lithosphere buckling induced by far‐field compressional tectonic processes and thereafter through deep mantle upwelling and epeirogeny tectonic processes. Key Points: The Tanzanian basement rocks record two significant cooling events at 340–220 Ma and 70 Ma Cooling events in Tanzania are contemporaneous with subsidence histories of the Congo basin The cooling and subsidence events suggest complex regional geodynamics during the Phanerozoic